Lacking sexual size dimorphism in some rodent species (Rodentia) in semi-desert region of Mongolia - Onolragchaa Ganbold; Rentsen Oyunbat; Ariunbold Jargalsaikhan; Ganchimeg J. Wingard (Mongolian Journal of Biological Sciences)
Body size differences between males and females of the same species are known as sexual size dimorphism (SSD). The male-biased and female-biased SSD have been reported simultaneously across numerous clades of mammals. In this study, we used long term monitoring measurement data of five species rodents to test existence of SSD in Ikh Nart Nature Reserve, Mongolia. We collected body measurements of Allactaga sibirica, Dipus sagitta, Meriones meridianus, Meriones ungiculatus, Phodopus roborovskii through years between 2007 and 2022. We found both significant male-biased and female-biased SSD in P.roborovskii (n = 661, t = 5.33; Df = 602.70; P < 0.001), and D.sagitta (n = 243, t = 2.14; Df = 192.9; P < 0.001), respectively. In addition, the little male-biased SSD (also known as non-significant but larger male) was obtained species from genus Meriones in this study. The non-significant SSD of both sexes could be related to other important secondary sexual displays (e.g., olfaction, ornamentation), which play significant role in sexual selection. Based on our findings, we would conclude that smaller species tend to have male-biased SSD (e.g., P. roborovskii; body length=6.20 cm), while larger species mostly have female-biased SSD (e.g., D. sagitta; body length=12.55 cm). However, indeed, we need to examine more species with different body size to make such certain conclusion.